Proximal Femur Fractures – How Decisive are Reduction and the Chosen Implant? - Gathen, Martin; Burger, Christof; Kasapovic, Adnan; Kabir, Koroush (Zeitschrift für Orthopädie und Unfallchirurgie, 2022)
Proximal femoral fractures are frequent and complex injuries requiring prompt and targeted care. Numerous treatment strategies have been described, some of which have been assessed and clinically implemented clinically. The aim of surgical is always the restoration of a pain-free and stable extremity. Mostly elderly patients are affected and treatment is associated with high postoperative complications and mortality rates. With increasing numbers of patients, the topic is of great medical and economic relevance. In this work, the choice of implants for the osteosynthesis of proximal femoral fractures – as depending on the fracture type – will be examined, as based on a review of current literature. Standard care includes cannulated screws, sliding hips screws and cephalomedullary nails. In addition, the influence of implant positioning, fracture reduction and additional measures such as cement augmentation are evaluated and discussed. Careful fracture reduction and the quality of implant positioning are paramount in order to avoid complications.
Keywords: hip fracture; proximal femur fracture; dynamic hip screw; proximal femur nail